Forecasting Conditional Covariance Matrices in High-Dimensional Time Series: A General Dynamic Factor Approach. Issue 1 (13th December 2022) - Trucíos, Carlos; Mazzeu, João H. G.; Hallin, Marc; Hotta, Luiz K.; Valls Pereira, Pedro L.; Zevallos, Mauricio
Abstract: Based on a General Dynamic Factor Model with infinite-dimensional factor space and MGARCH volatility models, we develop new estimation and forecasting procedures for conditional covariance matrices in high-dimensional time series. The finite-sample performance of our approach is evaluated via Monte Carlo experiments and outperforms the most alternative methods. This new approach is also used to construct minimum one-step-ahead variance portfolios for a high-dimensional panel of assets. The results are shown to match the results of recent proposals by Engle, Ledoit, and Wolf and achieve better out-of-sample portfolio performance than alternative procedures proposed in the literature.